The Role of the Police in Efforts to Overcome Sexual Violence Against Children - Abdul Hamid; Nanda Ivan Natsir; Ruli Ardiansyah; Titin Nurfatlah (JILPR Journal Indonesia Law and Policy Review, 2023)
Sexual violence is an act that can be categorized as abnormal sexual relationships and behaviors, resulting in serious harm and consequences for the victims. Cases of sexual violence against children in West Nusa Tenggara are quite common. Based on data from the West Nusa Tenggara Regional Police (POLDA), the Central Lombok Police Resort handles the most cases of sexual violence against children. The purpose of this research is to understand the role of the police in efforts to combat sexual violence against children and to identify the challenges faced by the Central Lombok Police Resort in preventing sexual violence against children. The research method used in this study is empirical legal research. The implementation of legal protection for children who are victims of sexual violence in West Lombok Regency is in accordance with Article 64 paragraph (3) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. In addition, obstacles in the implementation of legal protection for children who are victims of sexual violence in Central Lombok Regency consist of internal and external factors.